Excited-state prototropism of 7-hydroxy-4-methylcoumarin in [C(n)mim][BF4] series of ionic liquid-water mixtures: insights on reverse micelle-like water nanocluster formation - Beniwal, Vijay; Kumar, Anil; Pal, Haridas; Choudhury, Sharmistha Dutta (Photochemical & Photobiological Sciences, 2018)
This study explores the excited state prototropic behavior of the fluorophore, 7-hydroxy-4-methylcoumarin (7H4MC), in the [C(n)mim][BF4] (n = 2, 4, 6, 8, 10) series of ionic liquid (IL)-water mixtures at low water contents. In pure IL media, 7H4MC exists in the neutral form in both ground and excited states. However, on addition of water to the ILs, the excited neutral form of the dye is gradually converted to the anionic and the tautomeric species, leading to characteristic changes in the emission spectra. The similarity in the spectral features of 7H4MC in the IL-water system with that in a conventional reverse micelle system rather than with organic solvent-water mixtures, suggests that in the presence of water, the ILs are organized into reverse micelle-like structures with the consequent formation of confined water pockets. The results further suggest that formation of water nanoclusters and the ensuing changes in excited state prototropic behavior of the dye, is facilitated by increase in the alkyl chain length of the IL cation. These propositions are supported by time-resolved fluorescence studies. To the best of our knowledge this is the first report on proton transfer reaction in IL-water mixtures at low water contents. Considering that ILs are useful as solvents and surfactants, and IL-water mixtures in particular have applications in chemical extractions and biocatalysis, an understanding of the structural organization and water pool formation in these systems is quite important. The insights obtained from the prototropic transformations of 7H4MC are significant not only for fundamental self-assembly studies, but also for the development of ILs as chemical reaction media.